Functional characterization of two 3-dehydroquinases of AroQ1 and AroQ2 in the shikimate pathway and expression of genes for the type III secretion system in Ralstonia solanacearum - Zhang, Qingshan; Wu, Bofan; Han, Liangliang; Yu, Duan; Liang, Tao; Wang, Yan; Guo, Tao (Frontiers in Microbiology, 2023)
The shikimate pathway is a general route for the biosynthesis of aromatic amino acids (AAAs) in many microorganisms. A 3-dehydroquinase, AroQ, controls the third step of the shikimate pathway that catalyzes the formation of 3-dehydroquinate from 3-dehydroshikimate via a trans-dehydration reaction. Ralstonia solanacearum harbors two 3-dehydroquinases, AroQ1 and AroQ2, sharing 52% similarity in amino acids. Here, we demonstrated that two 3-dehydroquinases, AroQ1 and AroQ2, are essential for the shikimate pathway in R. solanacearum. The growth of R. solanacearum was completely diminished in a nutriment-limited medium with the deletion of both aroQ1 and aroQ2, while substantially impaired in planta. The aroQ1/2 double mutant was able to replicate in planta but grew slowly, which was ~4 orders of magnitude less than the parent strain to proliferate to the maximum cell densities in tomato xylem vessels. Moreover, the aroQ1/2 double mutant failed to cause disease in tomato and tobacco plants, whereas the deletion of either aroQ1 or aroQ2 did not alter the growth of R. solanacearum or pathogenicity on host plants. Supplementary shikimic acid (SA), an important intermediate of the shikimate pathway, substantially restored the diminished or impaired growth of aroQ1/2 double mutant in a limited medium or inside host plants. The necessity of AroQ1 and AroQ2 on the pathogenicity of solanacearum toward host plants was partially due to insufficient SA inside host plants. Moreover, the deletion of both aroQ1 and aroQ2 significantly impaired the expression of genes for the type III secretion system (T3SS) both in vitro and in planta. Its involvement in the T3SS was mediated through the well-characterized PrhA signaling cascade and was independent of growth deficiency under nutrient-limited conditions. Taken together, R. solanacearum 3-dehydroquinases play important roles in bacterial growth, the expression of the T3SS, and pathogenicity in host plants. These results could extend our insights into the understanding of the biological function of AroQ and the sophisticated regulation of the T3SS in R. solanacearum.